Knowledge of and Adherence to Hygiene Guidelines among Medical Students in Austria - Herbert, Verena G.; Schlumm, Paul; Kessler, Harald H.; Frings, Andreas (Interdisciplinary Perspectives on Infectious Diseases, 2013)
Background. Adherence to hygiene guidelines is of utmost importance for healthcare professionals. The aim of this study was to evaluate the knowledge on and the adherence to hygiene guidelines among medical students in Austria. Additionally, a possible difference between female and male students was investigated. Methods. An open paper-based survey among third-year medical students at the Medical University of Graz was conducted. The questionnaire consisted of 20 single-choice questions covering compliance with basic hygiene standards, self-rated knowledge of hygiene guidelines, and satisfaction with current hygiene education, equipment, and quality standards. Results. Of 192 medical students, 70% judged their knowledge of hygiene standards as “excellent” or “good”; however, only 49% reported adherence to hygiene guidelines and only 43% performed hygienic hand disinfection according to WHO guidelines. Of the respondents, 79% voted for a mandatory course on hygiene standards in medical education. No significant gender differences were observed. Conclusion. While the knowledge on hygiene guidelines appears to be good among medical students, adherence is limited and requires improvement. The need for an optimum education in hygiene is high.